Applying Focal Concerns and the Theory of Planned Behavior to the Decision-Making Process in Policing - Ishoy, Glen (2015)
This research used qualitative methods to investigate the police officer decision-making processes within the theoretical context of the focal concerns framework and the theory of planned behavior. This research had two primary goals. The first goal was to determine what similarities and differences exist in how ideas from the focal concerns framework manifest themselves in a policing context as compared to how they operate for judges when sentencing convicted offenders. The second goal of this research was to use ideas from the theory of planned behavior to elaborate the focal concerns framework into a functional theoretical model of police officer decision-making. While intuitively sound, the focal concerns perspective is in need of conceptual enhancements to operationalize the mechanisms through which the focal concerns identified are transformed into action. Interviews with police officers were conducted to elicit the considerations that police officers see as important to their decision-making process in order to develop a theory of police decision-making which incorporates concepts from the focal concerns framework and the theory of planned behavior. The results of this study indicate that although police officers share the same broad focal concerns as judges, the way these concerns manifest themselves in the execution of their duties is different for police officers. The results also indicate that the construct of intent from the theory of planned behavior may be a viable cognitive mechanism to connect ideas from the focal concerns framework with criminal justice outcomes, although other constructs from the theory were only found to be partially applicable. Theoretical implications of the findings and directions for future research are also discussed